Medical ethics argumentation: analysis of main topics about medical ethics in clinical practice dealt in national journals of Medicine and Bioethics 1998-2013 - Ramos Vergara, Paulina; Bedregal García, Paula (Acta Bioethica, 2017)
The aim of this investigation is to identify the main topics of the discussion about medical ethics in clinical practice in Chile. 143 articles in Chilean medical and bioethics journals were identified. They were put under a systematic study using comparison, codification and text analysis techniques of the Grounded Theory approach. 30 subjects were identified in the discussion, where the treatment of the ethics from a “professional deontology” predominates. Emergent speeches of an ethics that appeals to goods and values superiors to the professional duties in the search of the good of the patient can be found. The transformation of the context in which the clinical practice takes place is the background of the discussion.